Eddy‐Induced Near‐Surface Chlorophyll Anomalies in the Subtropical Gyres: Biomass or Physiology?. Issue 7 (9th April 2021) - He, Qingyou; Zhan, Haigang; Cai, Shuqun; Zhan, Weikang
Abstract: Satellite observations show higher near‐surface phytoplankton chlorophyll (Chl) in anticyclonic eddies (AEs) than in cyclonic eddies (CEs) in the subtropical gyres, which is opposite to the prevailing features in midlatitude oceans. Recent studies have attributed this anomalous effect solely to changes in phytoplankton biomass, therefore reached a conclusion that AEs are more productive than CEs, contrary to the conventional eddy pumping paradigm. Here, we show that the Chl variations are due mainly to physiological adjustments instead. The high Chl in AEs is mostly explained by photoacclimation to low‐light environment caused by deepened mixing and more rapid light attenuation, and vice versa for CEs. Such a scenario indicates that phytoplankton are likely more cellular pigmented, rather than more abundant, in the AEs than in the CEs. These findings invite us to rethink the effects of eddies on oceanic productivity and carbon cycling in the subtropical gyres. Plain Language Summary: Oceanic mesoscale eddies occupy a quarter of the global ocean surface. They have been widely documented to form and maintain high near‐surface phytoplankton chlorophyll (Chl) patches with horizontal scales of O (100 km) for months. This signal has long been interpreted as changes in phytoplankton abundance and primary production arising from changes in nutrient supply driven by eddy dynamics. However, Chl is not simply a measurement of phytoplankton abundance. It also reflects changes in intracellular pigmentation originate from light‐driven and/or nutrient‐driven physiological adjustments. Here, we show that physiological response is an important component of the Chl variability induced by eddies across the global ocean. Especially, in the subtropical gyres, the eddy‐driven Chl variability is more dominated by physiological adjustments than by the changes in phytoplankton biomass. For anticyclonic eddies in these regions, deepened mixing and more rapid light attenuation reduce the exposure of phytoplankton to light, upregulate the synthesis of intracellular Chl, thus resulting in higher Chl than in cyclonic eddies. In contrast, no apparent difference in phytoplankton carbon was detected between these two types of eddies. Such a decoupling response of phytoplankton Chl from biomass invites us to rethink the effects of eddies on oceanic productivity and carbon cycling. Key Points: Physiological adjustments make considerable contributions to the response of phytoplankton chlorophyll to eddies in the global ocean Eddy‐driven chlorophyll variability in the subtropical gyres is more dominated by changes in phytoplankton physiology than in biomass Photoacclimation plays an important role in the processes of physiological adjustments in eddies in the subtropical gyres